ANTIBACTERIAL ACTIVITY OF PURIFIED EXTRACT OF AFRICAN LEAVES (Vernonia amygdalina Delile) AGAINST Escherichia coli - Karlina, Nina; Septiyati, Tri Putri; Ahidin, Didin; Zam Zam, Muhammad Yani; Setyaningsih, Indah; Indriaty, Sulistiorini; Kunaedi, Aan; Supriyadi, Yadi (Universitas Muhammadiyah Magelang, 2024)
The African leaf (Vernonia amygdalina Delile) is an Indonesian plant used by the community as a traditional medicine. V.amygdalina contains active compounds such as flavonoids, tannins, saponins, and steroids which have antibacterial properties. This study aims to determine the antibacterial activity and the most effective concentration of purified extracts of V.amygdalina against the Escherichia coli bacteria. V.amygdalina simplicia was extracted using the maceration method. Ethanolic extract V.amygdalina was tested for the quality of the extract parameters and purified. Then, the purified extract V.amygdalina was tested for phytochemical screening and antibacterial activity against Escherichia coli bacteria by well-diffusion with concentrations of 30%, 40%, and 50%. The result of the quality parameter test for ethanolic extract V.amygdalina meets the requirements of specific and non-specific parameters. Purified extract V.amygdalina positively contains flavonoids, tannins, saponins, and steroids. Antibacterial activity of 0.05% chloramphenicol and purified extract V.amygdalina concentrations of 30%, 40%, and 50% against Escherichia coli bacteria had inhibition of 23.42 mm, 8.40± 0.315 mm, 9.44± 0.543 mm, and 11.59 ± 1,640 mm. The produced most effective inhibition was at a concentration of 50%. The results showed that the purified extract of V.amygdalina has antibacterial activity in the moderate to strong category, and the most effective concentration against Escherichia coli bacteria is the concentration of 50%.